Enseignement, recherche, poïésis - Kyle Conway (Communication)
In this paper, the author presents a different approach to research writing by first looking at the nature of the research being written. He calls into question a distinction all too often taken for granted, namely that between research and teaching, to shed light on the important links between the two. The experiential aspect of a course suffers the moment it is written down and the content set in stone. That is the first paradox. The second relates to the content itself. A course’s content is a stream of signs too dynamic for our conventional analytical tools. The third paradox concerns this setting-in-stone, which, no matter what, does not stop the course-as-text from becoming an experience once more. This is where the potential of teaching-as-research is fully realized. These analyses revisit the first two paradoxes before tackling the third in the conclusion, where the author describes how a course-as-text can become an event to be experienced once again.